Load-bearing masonry technology: success factors and challenges of implementation in the Malaysian construction industry - Mohd Nawi, Mohd Nasrun; Abdullah, Che Sobry; Ramli, Nor Azlinda; Zalazilah, Mohd Hanizan; Bahaudin, Ahmad Yusni (IJTech, 2018)
This study aims to identify the success factors and challenges of implementing load-bearing masonry (LBM) technology in the Malaysian construction industry. The success factors and challenges of implementing LBM technology have been identified in previous literature. Further, this research has been carried out in which interviews were conducted to explore the real-life construction situation in Malaysia. The findings indicate that the success factors for LBM-technology implementation are organizational readiness, good collaboration, easier to install, skilled labor, continuous improvement of knowledge, excellent work coordination, improved efficiency of construction work, and environmentally friendly methods. The issues faced by construction firms, however, are related to a lack of knowledge, expertise, and government incentives and promotion as well as a lack of local demand. Based on these findings, it can be agreed that all the factors gathered from the previous literature are significantly related to the success factors and challenges in this study. Further study should be performed to improve the understanding of success factors and challenges on LBM-technology implementation.